2000
DOI: 10.1034/j.1600-0676.2000.020004330.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma elimination of cholyl‐lysyl‐fluorescein (CLF): a pilot study in patients with liver cirrhosis

Abstract: CLF test clearly distinguished between the two analyzed groups and was more sensitive than routine liver function tests. The test appears safe, simple to perform and analyze and after validation in larger cohorts of patients may have the potential to become a useful dynamic test of liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…For example, although ABCB11 and ABCC2 protein levels and localization were found to be maintained in primary biliary cirrhosis stages I and II (Zollner et al, 2003(Zollner et al, , 2007, reduced protein levels and a disruption of canalicular localization have been reported for ABCC2 in advanced primary biliary cirrhosis (stages III and IV) (Kullak-Ublick et al, 2002;Kojima et al, 2003). In a pilot study CLF elimination was analyzed in liver cirrhosis patients and seemed to be impaired in comparison with healthy volunteers (Milkiewicz et al, 2000). Those cirrhotic patients suffered from high serum bilirubin and bile salt level, indicative of a cholestatic situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although ABCB11 and ABCC2 protein levels and localization were found to be maintained in primary biliary cirrhosis stages I and II (Zollner et al, 2003(Zollner et al, , 2007, reduced protein levels and a disruption of canalicular localization have been reported for ABCC2 in advanced primary biliary cirrhosis (stages III and IV) (Kullak-Ublick et al, 2002;Kojima et al, 2003). In a pilot study CLF elimination was analyzed in liver cirrhosis patients and seemed to be impaired in comparison with healthy volunteers (Milkiewicz et al, 2000). Those cirrhotic patients suffered from high serum bilirubin and bile salt level, indicative of a cholestatic situation.…”
Section: Discussionmentioning
confidence: 99%
“…Cholyl-L-lysyl-fluorescein (CLF) is a fluorescent bile salt and has been introduced as a potential agent for assessing in vivo liver function (Milkiewicz et al, 2000). However, the transport systems involved in hepatic handling of CLF have not been investigated in molecular detail so far.…”
mentioning
confidence: 99%
“…Fluorescently labeled bile salts have been suggested as liver function indicators on the basis of a pilot study that demonstrated reduced clearance of cholyllysyl-fluorescein (CLF) in patients with liver cirrhosis (Milkiewicz et al, 2000). CLF is not a substrate of the major bile salt transporters NTCP and bile salt export pump (BSEP), but of OATP1B3, weakly of OATP1B1, and of the efflux transporters MRP2 and MRP3 (table 1).…”
Section: Fluorescently Labeled Bile Saltsmentioning
confidence: 99%
“…Hence, transport proteins are key molecular components of the hepatocellular detoxification system (phase 0 and phase III) and consequently of liver function tests. Liver function tests utilizing exogenous indicators such as indocyanine green (ICG), bromosulphophthalein (BSP), fluorescent bile salt derivatives, agents for magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT), or breath tests have been developed to complement the use of endogenous indicators (de Graaf et al, 2010a;Milkiewicz et al, 2000;Millet et al, 2011;Sakka, 2007). Preoperative dynamic liver function tests are part of the routine assessment of patients scheduled for liver resection in many centers (Breitenstein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of drug inhibition of CLF transport has been used to discern cholestatic mechanisms [61,62], and a positive association has been demonstrated between cholestatic DILI in humans and inhibition of apical CLF efflux from rat hepatocytes in sandwich culture [63]. Moreover, CLF has been shown to have 100% sensitivity when used to detect liver cirrhosis in patient cohorts [64,65].…”
Section: Petmentioning
confidence: 99%